Chinese Firms' Entry to Export Markets : The Role of Foreign Export Spillovers - Mayneris, Florian; Poncet, Sandra (World Bank, Washington, DC, 2013)
In this paper, the effect of proximity to multinational exporters on the creation of new export linkages (the extensive margin of trade) is debated. Using panel data from Chinese customs for 1997-2007, the capacity for Chinese domestic firms to begin exporting new varieties to new markets is shown to respond positively to the export activity of neighboring foreign firms. These spillovers are shown to be product and country specific. This conclusion is robust to fixed effects and instrumental variable specifications that control for both supply and demand shocks that could bias the estimations. The impact is sizable. The marginal impact of product-country-specific foreign export spillovers is five times as large as the effect of a 10 percent increase in the demand for the product in the destination country. Foreign export spillovers are also shown to be primarily limited to ordinary trade activities. Overall, our findings suggest that even for a country with an important cost-advantage such as China, there is room for initiatives from policy-makers that will diffuse best practices regarding export experience among exporters.